Foreclosed Collateral as an Alternative for Bad Credit Settlement in Indonesia - Furqon, Muhammad Adam; Sulistyandari, Sulistyandari; Prihatinah, Tri Lisiani (Problems of legality, 2024)
Credit loans have the risk of not fulfilling payment obligations. Therefore it is necessary to bind collateral to get a repayment with collateral. if it cannot be anticipated anymore, then lousy credit will occur and must be resolved immediately, credit settlement usually uses the execution of mortgage rights. However, there are alternative settlements regulated in article 12 an of the law of the Republic of Indonesia number 10 of 1998 concerning banking law, namely foreclosed collateral in practice, there are problems regarding the implementation of foreclosed collateral by verdict number 183/pdt/2020/PT SMG and verdict number 24/pdt.g/2019/PN Pti. This study aimed to analyze the implementation of foreclosed collateral as a way to resolve the problem of bad loans. The research method used is normative, using secondary data obtained from library research, including primary, secondary and tertiary legal sources. Therefore, the implementation of the foreclosed collateral taken over by verdict Number 183/PDT/2020/PT Smg is valid because it is through a voluntary submission mechanism, and verdict Number 24/Pdt.G/2019/PN Pti is invalid because there is no agreement and has an impact on debtors and creditors feel harmed.